Further Validation of the Coach Identity Prominence Scale - Pope, J. Paige; Hall, Craig R. (Measurement in physical education and exercise science, 2014)
This study was designed to examine select psychometric properties of the Coach Identity Prominence Scale (CIPS), including the reliability, factorial validity, convergent validity, discriminant validity, and predictive validity. Coaches (N = 338) who averaged 37 (SD = 12.27) years of age, had a mean of 13 (SD = 9.90) years of coaching experience, and were currently coaching 46 different sports, served as the participants in this study. Participants completed a questionnaire that included four sections: Demographics, identity prominence (CIPS; Pope & Hall, 2014), motivation (Coach Motivation Questionnaire [CMQ]; McLean, Mallet, & Newcombe, 2012), and passion (The Passion Scale; Vallerand et al., 2003). The findings provided support for the various types of reliability and validity tested in the present study, with only partial support for discriminant validity. The CIPS may therefore serve as a viable option for researchers interested in further understanding the identity or psychological processes of coach.